Preparation process of infrared magnetic plant fiber fabric
Nanocellulose and TEMPO oxidation were extracted through H2O2 and HAc solution system, combined with Fe3O4 magnetic nanoparticles and SiO2 and ZnO nanoparticles, and Ag-Fe3O4 nanoplant fibers were prepared by electrospinning technology, which solved the uneven distribution of magnetic fibers in the prior art. and the problem of insufficient flame retardant performance, nanofiber preparation with high magnetization strength, good spinning properties and high infrared emissivity is achieved.
Patent Information
- Application Number
- CN202411187543.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
It is difficult to prepare Fe3O4 nanofibers with high magnetization strength, good spinning properties and high infrared emissivity in the prior art, and the distribution of magnetic nanoparticles in electrospinning method is uneven and the flame retardant and antibacterial properties of the fibers are insufficient.
Nanocellulose was extracted using H2O2 and HAc solution systems, and negatively charged nanofibers were prepared by TEMPO oxidation. Combined with the synergistic effect of Fe3O4 magnetic nanoparticles and SiO2 and ZnO nanoparticles, Ag-Fe3O4 nanoplant fibers were prepared by electrospinning process.
Ag-Fe3O4 nanoplant fibers with high magnetization strength, good spinning properties and high infrared emissivity were prepared, with excellent antibacterial properties and morphological properties, and solved the problems of uneven distribution of magnetic fibers and insufficient flame retardant properties.
Smart Images

Figure CN119121446A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation process of infrared magnetic plant fiber fabric, belonging to the new technical field. Background Art
[0002] Made from bamboo and urban green waste fibers (mango, bauhinia and banyan), combined with clean H 2 O 2 Cellulose is extracted using a HAc solution system to convert bamboo and waste fibers into nanocellulose materials. In functional textiles, electrospun nanofibers have greater flexibility in the selection of polymers and functional materials. They also have the characteristics of high specific surface area and high porosity, so they have a higher load capacity and can be used in functional textiles such as protective clothing, drug delivery, wound dressings, and filtration. Iron-based oxide magnetic fiber materials not only have excellent adsorption properties, but also have the advantages of large aspect ratio, self-support, non-agglomeration, and easy separation of magnetic materials in fiber morphology. They are widely used in water pollution treatment. Electrospinning is a commonly used technology for preparing fiber materials. The sol-gel method is used to synthesize the precursor spinning solution to produce Fe with high saturation magnetization. 3 O 4 Magnetic fiber is the most commonly used magnetic material. It has the advantages of high saturation magnetization, wide raw material sources, and environmental friendliness. It is an ideal adsorbent material for treating pollutants in wastewater. First, starting from the formation principle and spinnability of the precursor spinning solution, by adjusting the surface tension, conductivity, viscosity and other parameters of the spinning solution, Fe 3 O 4 Precursor spinning solution, combined with electrospinning technology and appropriate heat treatment process to prepare Fe with high saturation magnetization 3 O 4 This method is one of the few methods to prepare Fe 3 O 4 The electrospinning method overcomes the common co-spinning method for preparing Fe 3 O 4 The magnetic nanoparticles in electrospun fibers are unevenly distributed in the fibers and may even clog the spinning device during the spinning process. Summary of the invention
[0003] In view of the above problems, the present invention provides a flame retardant and antibacterial ecological fiber.
[0004] The first technical purpose of the present invention is to provide a method for preparing cleaner, more strongly negatively charged and easily dispersible oxidized nanofibers.
[0005] The second technical purpose of the present invention is to provide an Ag-Fe with high magnetization intensity, good spinnability and good infrared emissivity. 3 O 4Nanofiber preparation process.
[0006] The third technical purpose of the present invention is to provide an infrared Ag-Fe electrospinning method. 3 O 4 Preparation technology of nano plant fibers.
[0007] The present invention relates to a preparation process of an infrared magnetic plant fiber fabric, comprising: preparation of nanocellulose extraction, preparation of TEMPO oxidized nanofibers, Fe 3 O 4 Preparation of nanofiber spinning solution, preparation of oxidized nanofibers by high pressure homogenization, nano-Ag modified Fe 3 O 4 Fiber, infrared Ag-Fe 3 O 4 Nano plant fiber, electrospinning infrared Ag-Fe 3 O 4 Preparation of nano-plant fibers.
[0008] Preferably, step (1) preparation of nanocellulose extraction First, the boiled bamboo chips are placed in a solution of hydrogen peroxide and acetic acid, and kept in a constant temperature shaker at a certain temperature for a certain period of time. After the treatment, vacuum filtration is used to separate the solid and liquid. Finally, the fibers are fully washed with deionized water until they are neutral to obtain nanocellulose. Preferably, step (2) preparation of TEMPO oxidized nanofibers First, weigh the nanofibers prepared in step (1), add TEMPO, NaBr and NaClO, maintain a certain stirring speed during the oxidation process, start timing from the point where NaClO is added, and observe the change in the pH value of the system. Then, during the oxidation process, add NaOH solution dropwise until the pH value of the system is stabilized at a certain value, and record the volume of NaOH consumed. When the pH of the system is stabilized at a certain value and does not change within a certain period of time, it is considered that the reaction has reached the end point. Finally, add ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store them in a refrigerator, and balance the moisture to obtain oxidized nanofibers. Preferably, in step (3), Fe 3 O 4 Preparation of nanofiber spinning solution First, weigh Fe 3 O 4 The magnetic nanoparticles were added to the prepared oxidized nanofiber solution. After ultrasonic oscillation, the solution was placed in an ice bath and ultrasonicated with an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution to obtain Fe 3 O 4 Nanofiber spinning solution; As a preferred step, in step (4), nano-Ag is modified Fe 3 O 4 fiber First, take AgNO 3 and PVP were completely dissolved in DMF, and TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a reactor with a polytetrafluoroethylene lining and sealed. Then, it was kept in a constant temperature oven for a certain period of time and then taken out and cooled naturally. After sampling, the reactants were separated by an external magnetic field. Finally, they were washed with acetone and ethanol respectively, and then dried in a vacuum oven at a certain temperature to obtain Ag-Fe 3 O 4 Nanofibers; Preferably, step (5) infrared Ag-Fe 3 O 4 Nano plant fiber First, take SiO 2 and ZnO particles in a mixed solvent of DMF:THF, and magnetically stirred for a certain period of time. The mixed solution was placed in an ultrasonic cleaner to obtain a uniformly dispersed nanoparticle dispersion. Then, the Ag-Fe prepared in step (4) was added to the mixed solution. 3 O 4 Nanofibers, stirred at room temperature, obtained Ag-Fe 3 O 4 Nanofiber spinning solution, finally, infrared Ag-Fe 3 O 4 Nano plant fibers; Preferably, step (6) electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers First, the electrospinning process is carried out under certain voltage, ambient temperature and humidity conditions. Then, there is a certain distance between the needle and the collector, and a certain propulsion speed. Finally, the collected fibers are dried in a drying oven at a certain temperature overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber.
[0009] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) preparation of nanocellulose extraction The boiled bamboo pieces were placed in a solution of hydrogen peroxide and acetic acid, where hydrogen peroxide (H 2 O 2) content is 30-70%, acetic acid (HAc) content is 20-50%, and the solid-liquid ratio is 5-10:1-5. Keep warm in a constant temperature shaker at 50-70℃ for 6-24h, with a rotation speed of 100-150rpm. After the treatment, separate the solid and liquid by vacuum filtration, and fully wash the fiber with deionized water to obtain nanocellulose.
[0010] The invention has the advantages that bamboo is abundant in my country and making full use of its resources can alleviate the plight of my country's forest resource shortage. Compared with the traditional preparation mode, H 2 O 2 The method of extracting cellulose with HAc solution system is cleaner.
[0011] Preferably, step (2) preparation of TEMPO oxidized nanofibers 1-10 g of the nanofibers prepared in step (1) are weighed, the fiber concentration is 0-5%, the amount of TEMPO is 0.001-0.100 g, the amount of NaBr is 0-5 g, the amount of NaClO is 50-100 ml, and the stirring speed is maintained at 100-500 rpm during the oxidation process. The timing starts from the point where NaClO is added, and the change in the system pH is observed. During the oxidation process, 0-5 mol / L NaOH solution is added dropwise until the system pH stabilizes at about 5-10, and the volume of NaOH consumed is recorded at the same time. When the system pH stabilizes at about 5-10 and does not change within 0-10 min, it is considered that the reaction endpoint has been reached, and 0-100 ml of ethanol is added to terminate the reaction. The stirring is stopped, and the oxidized fibers are fully washed with deionized water and stored in a refrigerator at 0-10° C. to balance the moisture to obtain oxidized nanofibers.
[0012] The advantage of the present invention is that the TEMPO oxidation system is highly selective and can catalytically oxidize the primary hydroxyl groups on cellulose C6 into carboxyl groups, making the fibers strongly negatively charged and easy to disperse in water. The oxidized fibers can be subjected to appropriate mechanical treatment to obtain a nanocellulose suspension.
[0013] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, in step (3), Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles are added to the prepared oxidized nanofiber solution, and after ultrasonic oscillation for 0-5 hours, the solution is placed in an ice bath and ultrasonicated with an ultrasonic cell crusher for 0-60 minutes to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution.
[0014] The present invention has the advantage that Fe3 O 4 Nanoparticles have the advantages of high magnetic intensity at room temperature, wide sources, non-toxicity, good biocompatibility, simple preparation and low cost.
[0015] As a preferred step, in step (4), nano-Ag is modified Fe 3 O 4 fiber Take 0.100-0.110gAgNO 3 1-2g PVP was completely dissolved in 10-30mL DMF, and 30-60mg TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a reaction kettle with a polytetrafluoroethylene lining and sealed, and kept in a constant temperature oven at 100-200°C for 1-5 hours, then taken out, cooled naturally, and the reactants were separated by an external magnetic field after sampling, washed with acetone and ethanol for 1-5 times, and then placed in a vacuum oven at 50-100°C for 10-20 hours to obtain Ag-Fe 3 O 4 Nanofibers.
[0016] The invention has the advantage that the fiber surface is modified with nano-Ag by a hydrothermal method to prepare a composite fiber with strong magnetism and good photocatalytic performance, the light absorption capacity is greatly enhanced, and the absorption band is red-shifted and extended to the visible light region.
[0017] The third technical purpose of the present invention is achieved through the following technical solutions: Step (5) Infrared Ag-Fe 3 O 4 Nano plant fiber Take SiO 2 0.6 g of each of Ag-Fe and ZnO particles are dissolved in a mixed solvent of DMF:THF=1-5:1-5, stirred magnetically for 5-15 min, and the mixed solution is placed in an ultrasonic cleaner for 20-40 min to obtain a uniformly dispersed nanoparticle dispersion. 2-3 g of the Ag-Fe prepared in step (4) is added to the mixed solution. 3 O 4 Nanofibers were stirred at room temperature for 2-10h to obtain Ag-Fe 3 O 4 Nanofiber spinning solution.
[0018] The present invention has the advantage that SiO 2 The synergistic effect of ZnO particles can effectively enhance the far-infrared emission function of the fabric. The nanofiber yarn has good morphology and mechanical properties, as well as high far-infrared emissivity and excellent antibacterial properties.
[0019] Step (6) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 10-15 kV, ambient temperature 20-30 °C and humidity 30-50%, the distance between the needle and the collector was about 10-20 cm, the propulsion speed was 0.1-1.5 mh, and the collected fibers were dried in a drying oven at 30-60 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber.
[0020] The invention has the advantages that electrostatic spinning has become one of the main ways to effectively prepare nanofiber materials due to its simple manufacturing device, low spinning cost, a wide variety of spinnable materials, and controllable process.
[0021] In summary, the present invention has the following beneficial effects: 1. The advantage of the present invention is that bamboo is abundant in my country and compared with the traditional preparation mode, H 2 O 2 The method of extracting cellulose with the HAc solution system is cleaner; 2. The present invention has the advantage that the TEMPO oxidation system is highly selective and can catalytically oxidize the primary hydroxyl groups on cellulose C6 into carboxyl groups, making the fibers strongly negatively charged and easy to disperse in water. The oxidized pulp can be subjected to appropriate mechanical treatment to obtain a nanocellulose suspension; 3. The advantage of the present invention is that Fe 3 O 4 Nanoparticles have many advantages due to their high magnetic intensity at room temperature, wide sources, non-toxicity, good biocompatibility, simple preparation and low cost; 4. The present invention has the advantages that the nano-Ag modification of the fiber surface is carried out by a hydrothermal method to prepare a composite fiber with strong magnetism and good photocatalytic performance, the light absorption capacity is greatly enhanced, and the absorption band is red-shifted and extended to the visible light region; 5. The present invention has the advantage that SiO 2 The synergistic effect of ZnO particles can effectively enhance the far-infrared emission function of the fabric. The nanofiber yarn has good morphology and mechanical properties, as well as high far-infrared emissivity and excellent antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a process flow chart for preparing infrared magnetic plant fiber fabric. DETAILED DESCRIPTION
[0023] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0024] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products. Example 1
[0025] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo chips were placed in a hydrogen peroxide and acetic acid system solution, wherein the hydrogen peroxide content was 40%, the acetic acid content was 20%, and the solid-liquid ratio was 5:1. The solution was kept in a constant temperature shaker at 50°C for 10 hours at a speed of 100 rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 2 g of the nanofibers prepared in step (1), with a fiber concentration of 1%, a TEMPO dosage of 0.050 g, a NaBr dosage of 3 g, and a NaClO dosage of 50 ml. During the oxidation process, maintain a stirring speed of 200 rpm, start timing from the point where NaClO is added, observe the change in the system pH, drop 1 mol / L NaOH solution during the oxidation process until the system pH stabilizes at about 8, and record the volume of NaOH consumed. When the system pH stabilizes at about 8 and does not change within 7 minutes, it is considered that the reaction endpoint has been reached, add 40 ml of ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store in a refrigerator at 0-10°C to balance the moisture, and obtain oxidized nanofibers; Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles were added to the prepared oxidized nanofiber solution, and after ultrasonic oscillation for 0.5 h, the solution was placed in an ice bath and ultrasonicated for 5 min using an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution; Step (4) Nano-Ag modified Fe 3 O 4 fiber Take 0.100gAgNO 3 1.0 g PVP was completely dissolved in 20 mL DMF, and 35 mg TiO 2 Magnetic fiber, Fe prepared in step (3)3 O 4 The nanofiber spinning solution was transferred into a sealed reactor with a polytetrafluoroethylene liner, kept in a constant temperature oven at 140°C for 1-5 hours, taken out, cooled naturally, and sampled. The reactants were separated by an external magnetic field, washed twice with acetone and ethanol, respectively, and then dried in a vacuum oven at 60°C for 11 hours to obtain Ag-Fe 3 O 4 Nanofibers; Step (5) Infrared Ag-Fe 3 O 4 Nano plant fiber Take SiO 2 0.6 g of each of the Ag-Fe prepared in step (4) was added to a mixed solvent of DMF:THF = 1:2, and stirred magnetically for 5 min. The mixed solution was placed in an ultrasonic cleaner for 20-40 min to obtain a uniformly dispersed nanoparticle dispersion. 2 g of the Ag-Fe prepared in step (4) was added to the mixed solution. 3 O 4 Nanofibers were stirred at room temperature for 2 h to obtain Ag-Fe 3 O 4 Nanofiber spinning solution, and then prepared into infrared Ag-Fe 3 O 4 Nano plant fibers; Step (6) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 10 kV, ambient temperature 20-30 °C and humidity 30%, the distance between the needle and the collector was about 10 cm, the propulsion speed was 0.5 mh, and the collected fibers were dried in a drying oven at 30 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber. Example 2
[0026] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo pieces were placed in a hydrogen peroxide and acetic acid solution, where the hydrogen peroxide content was 45% and the acetic acid content was 24%. The solid-liquid ratio was 6:3. The mixture was kept in a 55°C constant temperature shaker for 6-24 hours at a speed of 110 rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 4 g of the nanofibers prepared in step (1), with a fiber concentration of 1.5%, a TEMPO dosage of 0.065 g, a NaBr dosage of 1 g, and a NaClO dosage of 65 ml. During the oxidation process, maintain a stirring speed of 350 rpm, start timing from the point where NaClO is added, observe the change in the system pH, drop 1.5 mol / L NaOH solution during the oxidation process until the system pH stabilizes at about 8.5, and record the volume of NaOH consumed. When the system pH stabilizes at about 8.5 and does not change within 8 min, it is considered that the reaction has reached the end point, add 65 ml of ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store in a refrigerator at 5°C to balance the moisture, and obtain oxidized nanofibers. Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles are added to the prepared oxidized nanofiber solution. After ultrasonic oscillation for 3 hours, the solution is placed in an ice bath and ultrasonicated for 30 minutes using an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution. Step (4) Nano-Ag modified Fe 3 O 4 fiber Take 0.115g AgNO 3 and 1.4 g PVP were completely dissolved in 10-30 mL DMF, and 45 mg TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a sealed reactor with a polytetrafluoroethylene liner, kept in a constant temperature oven at 170°C for 1-5 hours, taken out, cooled naturally, and sampled to separate the reactants using an external magnetic field. The reactants were washed with acetone and ethanol for 4 times, respectively, and then dried in a vacuum oven at 70°C for 14 hours to obtain Ag-Fe 3 O 4 Nanofibers; Step (5) Infrared Ag-Fe 3 O 4 Nano plant fiber Take 0.6 g of SiO2 and ZnO particles respectively in a mixed solvent of DMF:THF=2:3, stir magnetically for 12 min, and place the mixed solution in an ultrasonic cleaner for 35 min to obtain a uniformly dispersed nanoparticle dispersion. Add 2.6 g of the Ag-Fe prepared in step (4) to the mixed solution. 3 O 4 Nanofibers were stirred at room temperature for 5 h to obtain Ag-Fe 3 O4 Nanofiber spinning solution, and then prepared into infrared Ag-Fe 3 O 4 Nano plant fibers; Step (6) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 13 kV, ambient temperature 26 °C and humidity 40%. The distance between the needle and the collector was about 17 cm, the propulsion speed was 1.5 mh, and the collected fibers were dried in a drying oven at 60 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber. Example 3
[0027] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo pieces were placed in a hydrogen peroxide and acetic acid solution, where the hydrogen peroxide content was 50% and the acetic acid content was 30%. The solid-liquid ratio was 7:2. The mixture was kept in a constant temperature shaker at 50-70℃ for 14 hours at a speed of 120rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 5 g of the nanofibers prepared in step (1), with a fiber concentration of 0.5%, a TEMPO dosage of 0.070 g, a NaBr dosage of 1 g, and a NaClO dosage of 55 ml. During the oxidation process, maintain a stirring speed of 250 rpm, start timing from the point where NaClO is added, observe the change in the system pH, drop 1 mol / L NaOH solution during the oxidation process until the system pH stabilizes at about 9.5, and record the volume of NaOH consumed. When the system pH stabilizes at about 9.5 and does not change within 9 minutes, it is considered that the reaction has reached the end point, add 55 ml of ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store in a refrigerator at 5°C to balance the moisture, and obtain oxidized nanofibers; Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles are added to the prepared oxidized nanofiber solution. After ultrasonic oscillation for 1.5 hours, the solution is placed in an ice bath and ultrasonicated for 15 minutes using an ultrasonic cell crusher to evenly disperse the magnetic nanoparticles in the oxidized nanofiber solution. Step (4) Nano-Ag modified Fe 3 O4 fiber Take 0.110gAgNO 3 and 1.6 g PVP were completely dissolved in 20 mL DMF, and 55 mg TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a sealed reactor with a polytetrafluoroethylene liner, kept in a constant temperature oven at 150°C for 3 hours, taken out, cooled naturally, and sampled. The reactants were separated by an external magnetic field, washed with acetone and ethanol three times, and then dried in a vacuum oven at 85°C for 10 hours to obtain Ag-Fe 3 O 4 Nanofibers; Step (5) Infrared Ag-Fe 3 O 4 Nano plant fiber Take SiO 2 0.6 g of each of the Ag-Fe prepared in step (4) was added to the mixed solution. The mixture was stirred magnetically for 12 min and then placed in an ultrasonic cleaner for 35 min to obtain a uniformly dispersed nanoparticle dispersion. 3 O 4 Nanofibers were stirred at room temperature for 5 h to obtain Ag-Fe 3 O 4 Nanofiber spinning solution, and then prepared into infrared Ag-Fe 3 O 4 Nano plant fibers; Step (6) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 11 kV, ambient temperature 25 °C and humidity 40%. The distance between the needle and the collector was about 14 cm, the propulsion speed was 1.2 mh, and the collected fibers were dried in a drying oven at 55 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber. Example 4
[0028] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo pieces were placed in a hydrogen peroxide and acetic acid system solution, in which the hydrogen peroxide content was 50% and the acetic acid content was 30%. The solid-liquid ratio was 8:1. The mixture was kept in a 65°C constant temperature shaker for 12 hours at a speed of 120 rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water until neutral to obtain nanocellulose.
[0029] Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 5 g of the nanofibers prepared in step (1), with a fiber concentration of 1%, a TEMPO dosage of 0.075 g, a NaBr dosage of 0.5 g, and a NaClO dosage of 60 ml. During the oxidation process, maintain a stirring speed of 300 rpm. Start timing from the point where NaClO is added, observe the change in the system pH, and add 0.5 mol / L NaOH solution during the oxidation process until the system pH stabilizes at around 10.0, while recording the volume of NaOH consumed. When the system pH stabilizes at around 10.0 and does not change within 10 minutes, it is considered that the reaction endpoint has been reached, and 50 ml of ethanol is added to terminate the reaction. Stop stirring, wash the oxidized fibers thoroughly with deionized water, and store them in a refrigerator at 4°C to balance the moisture to obtain oxidized nanofibers.
[0030] Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles are added to the prepared oxidized nanofiber solution. After ultrasonic oscillation for 1 hour, the solution is placed in an ice bath and ultrasonicated for 10 minutes using an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution.
[0031] Step (4) Nano-Ag modified Fe 3 O 4 fiber Take 0.108gAgNO 3 and 1.8 g PVP were completely dissolved in 25 mL DMF, and 50 mg TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a sealed reactor with a polytetrafluoroethylene liner, kept in a constant temperature oven at 160°C for 2 hours, taken out, cooled naturally, and sampled. The reactants were separated by an external magnetic field, washed with acetone and ethanol three times, and then dried in a vacuum oven at 80°C for 12 hours to obtain Ag-Fe 3 O 4 Nanofibers.
[0032] Step (5) Infrared Ag-Fe 3 O 4 Nano plant fiber Take SiO 20.6 g of each of the Ag-Fe prepared in step (4) was added to the mixed solution. The mixture was stirred magnetically for 10 min and then placed in an ultrasonic cleaner for 30 min to obtain a uniformly dispersed nanoparticle dispersion. 2.8 g of the Ag-Fe prepared in step (4) was added to the mixed solution. 3 O 4 The nanofibers were stirred at room temperature for 6 h to obtain a PU spinning solution with a mass fraction of 14%.
[0033] Step (6) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 12kV, ambient temperature 20-30℃ and humidity 30-50%. The distance between the needle and the collector was about 15cm, the propulsion speed was 1.0mh, and the collected fibers were dried in a drying oven at 50℃ overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber. Comparative Example 1
[0034] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo chips were placed in a hydrogen peroxide and acetic acid system solution, wherein the hydrogen peroxide content was 70%, the acetic acid content was 50%, and the solid-liquid ratio was 10:5. The solution was kept in a constant temperature shaker at 70°C for 24 hours at a rotation speed of 150 rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 5 g of the nanofibers prepared in step (1), with a fiber concentration of 1%, a TEMPO dosage of 0.075 g, a NaBr dosage of 0.5 g, and a NaClO dosage of 60 ml. During the oxidation process, the stirring speed is maintained at 300 rpm. The timing is started from the point where NaClO is added, and the pH change of the system is observed. During the oxidation process, 0.5 mol / L NaOH solution is added dropwise until the pH of the system is stabilized at about 10.0. At the same time, the volume of NaOH consumed is recorded. When the pH of the system is stabilized at about 10.0 and does not change within 10 minutes, it is considered that the reaction has reached the end point. 50 ml of ethanol is added to terminate the reaction, and stirring is stopped. The oxidized fibers are fully washed with deionized water and stored in a refrigerator at 4°C to balance the moisture to obtain oxidized nanofibers. Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4The magnetic nanoparticles are added to the prepared oxidized nanofiber solution, and after ultrasonic oscillation for 5 hours, the solution is placed in an ice bath and ultrasonicated for 60 minutes using an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution; Step (4) Nano-Ag modified Fe 3 O 4 fiber Take 0.110gAgNO 3 2g PVP was completely dissolved in 30mL DMF, and 60mg TiO 2 Magnetic fiber, Fe prepared in step (3) 3 O 4 The nanofiber spinning solution was transferred into a sealed reactor with a polytetrafluoroethylene liner, kept in a constant temperature oven at 200°C for 5 hours, then taken out, cooled naturally, and sampled. The reactants were separated by an external magnetic field, washed with acetone and ethanol for 5 times, and then dried in a vacuum oven at 100°C for 20 hours to obtain Ag-Fe 3 O 4 Nanofibers; Step (5) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 15 kV, ambient temperature 30 °C and humidity 50%, the distance between the needle and the collector was about 20 cm, the propulsion speed was 1.5 mh, and the collected fibers were dried in a drying oven at 60 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber. Comparative Example 2
[0035] Step (1) Preparation of Nanocellulose Extraction The boiled bamboo pieces were placed in a hydrogen peroxide and acetic acid system solution, wherein the hydrogen peroxide content was 30%, the acetic acid content was 50%, and the solid-liquid ratio was 10:1. The mixture was kept in a 50°C constant temperature shaker for 24 hours at a speed of 150 rpm. After the treatment, the solid and liquid were separated by vacuum filtration, and the fibers were fully washed with deionized water to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers Weigh 1-10 g of the nanofibers prepared in step (1), with a fiber concentration of 5%, a TEMPO dosage of 0.001, a NaBr dosage of 0.5 g, and a NaClO dosage of 50 ml. During the oxidation process, maintain a stirring speed of 100 rpm, start timing from the point where NaClO is added, observe the change in the system pH, drop 0-5 mol / L NaOH solution during the oxidation process until the system pH stabilizes at about 10, and record the volume of NaOH consumed. When the system pH stabilizes at about 10 and does not change within 10 minutes, it is considered that the reaction has reached the end point, add 100 ml of ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store in a refrigerator at 0-10°C to balance the moisture, and obtain oxidized nanofibers; Step (3) Fe 3 O 4 Preparation of nanofiber spinning solution Weigh different amounts of Fe 3 O 4 The magnetic nanoparticles are added to the prepared oxidized nanofiber solution, and after ultrasonic oscillation for 5 hours, the solution is placed in an ice bath and ultrasonicated for 0-60 minutes using an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution; Step (4) Infrared Ag-Fe 3 O 4 Nano plant fiber Take SiO 2 0.6 g of each of the Ag-Fe prepared in step (3) was added to the mixed solution. The mixture was stirred magnetically for 15 min and then placed in an ultrasonic cleaner for 40 min to obtain a uniformly dispersed nanoparticle dispersion. 3 O 4 Nanofibers were stirred at room temperature for 2 h to obtain Ag-Fe 3 O 4 Nanofiber spinning solution, and then prepared into infrared Ag-Fe 3 O 4 Nano plant fibers; Step (5) Electrospinning infrared Ag-Fe 3 O 4 Preparation of Nano-Plant Fibers The electrospinning process was carried out under the conditions of voltage 10 kV, ambient temperature 20 °C and humidity 30%, the distance between the needle and the collector was about 10 cm, the propulsion speed was 0.1 mh, and the collected fibers were dried in a drying oven at 30 °C overnight to obtain electrospun infrared Ag-Fe 3 O 4 Nano plant fiber.
[0036] Comparison of detection experiments The fibers obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested, and the specific testing methods are as follows: Infrared emissivity The principle of infrared spectroscopy to measure infrared emissivity is based on the interaction of objects with infrared radiation. When an object is exposed to external infrared radiation, part of the energy will be absorbed, while the other part will be emitted by the surface of the object. By measuring the intensity of infrared radiation emitted by an object, we can calculate the infrared emissivity.
[0037] Digital Viscometer Study the effect of the proportion of ethanol in the solvent and the amount of solvent on key parameters of the spinning solution, such as surface tension, conductivity and viscosity. By adjusting these variables, we can gain a deeper understanding of their role and influence on the properties of the spinning solution.
[0038] Conductivity meter test Place two parallel plates in the solution to be tested, apply a certain potential (usually a sinusoidal voltage) to both ends of the plates, and then measure the current flowing between the plates. According to Ohm's law, when the electrode constant (J) is known and the solution resistance (R) or conductivity (G) is measured, the conductivity can be calculated.
[0039] Table 1 Infrared emissivity
[0040] As can be seen from Table 1, Example 4 is the best, while Comparative Example 2 is relatively poor. The comparative example data is obviously smaller than that of the example, indicating that the embedded SiO 2 The fabrics containing ZnO and ZnO have higher infrared emission efficiency. At the same time, the infrared Ag-Fe electrospinning fabrics with the same addition amount have a higher infrared emission efficiency. 3 O 4 The infrared emissivity of nano-plant fibers is higher than the far-infrared emissivity of single materials. This result shows that SiO 2 The synergistic effect with ZnO nanoparticles can effectively improve the infrared emissivity of the fabric, which has the advantage of better infrared emissivity.
[0041] Table 2 Digital Viscometer
[0042] As shown in Table 2, Example 4 is the best, while Comparative Example 2 is relatively poor. The comparative example data is obviously smaller than that of the embodiment. Reducing the amount of ethanol will increase the viscosity of the spinning solution, which is beneficial to improving the yield of nanofibers, while increasing the adhesion between fibers and achieving more precise microstructure control. It can be seen from the data that electrospinning infrared Ag-Fe 3 O 4 Nano-plant fiber spinning solution has good spinnability and it is easy to obtain fluffy fibers.
[0043] Table 3 Conductivity meter test
[0044] As shown in Table 3, Example 4 is the best, while Comparative Example 2 is relatively poor. The comparative example data is obviously smaller than that of the example, indicating that the electrospinning infrared Ag-Fe 3 O 4 Nano-plant fibers can improve the viscosity, surface tension and conductivity of the spinning solution by using a mixture of water and ethanol as a solvent and adjusting the proportion of ethanol in the solvent and the amount of the solvent to improve its spinnability, and have the advantage of high conductivity.
[0045] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. The preparation process of infrared magnetic plant fiber fabric is characterized by : Preparation of nanocellulose extraction, preparation of TEMPO oxidized nanofibers, preparation of Fe3O4 nanofiber spinning solution, preparation of oxidized nanofibers by high pressure homogenization, nano-Ag modified Fe3O4 fibers, infrared Ag-Fe3O4 nano-plant fibers, and preparation of electrospinning infrared Ag-Fe3O4 nano-plant fibers.
2. The preparation process of the infrared magnetic plant fiber fabric according to claim 1, characterized in that : Step (1) Preparation of Nanocellulose Extraction First, the boiled bamboo chips are placed in a solution of hydrogen peroxide and acetic acid, and kept in a constant temperature shaker at a certain temperature for a certain period of time. After the treatment, vacuum filtration is used to separate the solid and liquid. Finally, the fibers are fully washed with deionized water until they are neutral to obtain nanocellulose. Step (2) Preparation of TEMPO-oxidized nanofibers First, weigh the nanofibers prepared in step (1), add TEMPO, NaBr and NaClO, maintain a certain stirring speed during the oxidation process, start timing from the point where NaClO is added, and observe the change in the pH value of the system. Then, during the oxidation process, add NaOH solution dropwise until the pH value of the system is stabilized at a certain value, and record the volume of NaOH consumed. When the pH of the system is stabilized at a certain value and does not change within a certain period of time, it is considered that the reaction has reached the end point. Finally, add ethanol to terminate the reaction, stop stirring, and wash the oxidized fibers thoroughly with deionized water, store them in a refrigerator, and balance the moisture to obtain oxidized nanofibers. Step (3) Preparation of Fe3O4 nanofiber spinning solution Firstly, Fe3O4 magnetic nanoparticles are weighed and added to the prepared oxidized nanofiber solution. After ultrasonic oscillation, the solution is placed in an ice bath and ultrasonicated with an ultrasonic cell crusher to uniformly disperse the magnetic nanoparticles in the oxidized nanofiber solution to obtain Fe3O4 nanofiber spinning solution. Step (4) Nano-Ag modified Fe3O4 fiber First, AgNO3 and PVP are completely dissolved in DMF, TiO2 magnetic fibers are added, the Fe3O4 nanofiber spinning solution prepared in step (3) is transferred into a reaction kettle with a polytetrafluoroethylene lining and sealed, then, it is kept in a constant temperature oven at a certain temperature for a certain period of time, taken out, cooled naturally, and the reactants are separated by an external magnetic field after sampling, and finally, they are washed with acetone and ethanol respectively, and then placed in a vacuum oven at a certain temperature for drying to obtain Ag-Fe3O4 nanofibers; Step (5) Infrared Ag-Fe3O4 nano-plant fiber First, SiO2 and ZnO particles are placed in a mixed solvent of DMF:THF, and magnetically stirred for a certain period of time. The mixed solution is placed in an ultrasonic cleaner to obtain a uniformly dispersed nanoparticle dispersion. Then, the Ag-Fe3O4 nanofibers prepared in step (4) are added to the mixed solution, and stirred at room temperature to obtain an Ag-Fe3O4 nanofiber spinning solution. Step (6) Preparation of infrared Ag-Fe3O4 nano-plant fibers by electrospinning The electrospinning process is carried out under certain voltage, ambient temperature and humidity conditions, then, there is a certain distance between the needle and the collector, and a certain propulsion speed, and finally, the collected fibers are dried overnight in a drying oven at a certain temperature to obtain electrospun infrared Ag-Fe3O4 nano-plant fibers.
3. The preparation process of the infrared magnetic plant fiber fabric according to claim 2, characterized in that : Step (1) Preparation of Nanocellulose Extraction The boiled bamboo chips are placed in a hydrogen peroxide and acetic acid system solution, wherein the hydrogen peroxide (H2O2) content is 30-70%, the acetic acid (HAc) content is 20-50%, and the solid-liquid ratio is 5-10:1-5. The solution is kept warm in a constant temperature shaker at 50-70°C for 6-24 hours at a rotation speed of 100-150rpm. After the treatment, the solid and liquid are separated by vacuum filtration, and the fibers are fully washed with deionized water to obtain nanocellulose.
4. The preparation process of the infrared magnetic plant fiber fabric according to claim 3, characterized in that : Step (2) Preparation of TEMPO-oxidized nanofibers 1-10 g of the nanofibers prepared in step (1) are weighed, the fiber concentration is 0-5%, the amount of TEMPO is 0.001-0.100 g, the amount of NaBr is 0-5 g, the amount of NaClO is 50-100 ml, and the stirring speed is maintained at 100-500 rpm during the oxidation process. The timing starts from the point where NaClO is added, and the change in the system pH is observed. During the oxidation process, 0-5 mol / L NaOH solution is added dropwise until the system pH stabilizes at about 5-10, and the volume of NaOH consumed is recorded at the same time. When the system pH stabilizes at about 5-10 and does not change within 0-10 min, it is considered that the reaction endpoint has been reached, and 0-100 ml of ethanol is added to terminate the reaction. The stirring is stopped, and the oxidized fibers are fully washed with deionized water and stored in a refrigerator at 0-10° C. to balance the moisture to obtain oxidized nanofibers.
5. The preparation process of the infrared magnetic plant fiber fabric according to claim 4, characterized in that : Step (3) Preparation of Fe3O4 nanofiber spinning solution Weigh the same amount of Fe3O4 magnetic nanoparticles, add them to the prepared oxidized nanofiber solution, and after ultrasonic oscillation for 0-5 hours, place the solution in an ice bath and ultrasonicate it with an ultrasonic cell crusher for 0-60 minutes to evenly disperse the magnetic nanoparticles in the oxidized nanofiber solution.
6. The preparation process of the infrared magnetic plant fiber fabric according to claim 5, characterized in that : Step (4) Nano-Ag modified Fe3O4 fiber Take 0.100-0.110gAgNO3 and 1-2gPVP and completely dissolve them in 10-30mL DMF, add 30-60mgTiO2 magnetic fiber, transfer the Fe3O4 nanofiber spinning solution prepared in step (3) into a reaction kettle with a polytetrafluoroethylene liner and seal it, keep it in a constant temperature oven at 100-200°C for 1-5h, then take it out, cool it naturally, take samples and separate the reactants with an external magnetic field, wash them with acetone and ethanol for 1-5 times respectively, and then place them in a vacuum oven at 50-100°C for drying for 10-20h to obtain Ag-Fe3O4 nanofibers.
7. The preparation process of the infrared magnetic plant fiber fabric according to claim 6, characterized in that : Step (5) Infrared Ag-Fe3O4 nano-plant fiber Take 0.6 g of SiO2 and ZnO particles respectively and put them into a mixed solvent of DMF:THF=1-5:1-5, stir them magnetically for 5-15 min, place the mixed solution in an ultrasonic cleaner for 20-40 min to obtain a uniformly dispersed nanoparticle dispersion, add 2-3 g of Ag-Fe3O4 nanofibers prepared in step (4) to the mixed solution, stir them at room temperature for 2-10 h, and obtain Ag-Fe3O4 nanofiber spinning solution.
8. The preparation process of the infrared magnetic plant fiber fabric according to claim 7, characterized in that : Step (6) Preparation of infrared Ag-Fe3O4 nano-plant fibers by electrospinning The electrospinning process was carried out under the conditions of voltage 10-15 kV, ambient temperature 20-30 °C and humidity 30-50%, the distance between the needle and the collector was about 10-20 cm, the propulsion speed was 0.1-1.5 mh, and the collected fibers were dried in a drying oven at 30-60 °C overnight to obtain electrospun infrared Ag-Fe3O4 nano-plant fibers.
Citation Information
Patent Citations
Far infrared magnetic fiber and application and manufacturing method thereof
CN101445969A
Preparation method for nano-cellulose
CN104047198A
Method for preparing magnetic cellulose composite fiber
CN106400185A
Preparation method of Fe3O4 / nano-cellulose aerogel negative electrode material
CN108832105A
Preparation method of magnetic nano short fibers loaded with silver nanoparticles and application thereof
CN114082443A
